In proven deep vein thrombosis, a low positive D-Dimer score is a strong negative predictor for associated malignancy - Rege, Kanchan P.; Jones, Sue; Day, Jane; Hoggarth, Catherine E. (Thrombosis and Haemostasis, 2004)
D-Dimer measurements are being increasingly used for negative prediction of deep vein thrombosis (DVT). At our institution, clinical score, D-Dimer assay, plethysmography and, if necessary, Doppler ultrasound are used to secure the diagnosis. We collected the data from 100 consecutive patients proven to have DVT. We examined their medical case notes at diagnosis for concurrent clinical conditions and one year later to look for documented evidence of malignancy. Twenty-two of the 66 patients with D-Dimers greater than 1000 ng/ml were diagnosed with a cancer compared with only 2 of the 34 patients with a presenting D-Dimer score of less than 1000 ng/ml. We propose that a D-Dimer score of less than 1000 ng/ml in proven DVT is a strong negative predictor for malignancy (p = 0.0025).
Keywords: D-Dimers; malignancy; deep vein thrombosis (DVT)